2016
DOI: 10.1088/0963-0252/25/3/035006
|View full text |Cite
|
Sign up to set email alerts
|

2D fluid model analysis for the effect of 3D gas flow on a capacitively coupled plasma deposition reactor

Abstract: The wide applicability of capacitively coupled plasma (CCP) deposition has increased the interest in developing comprehensive numerical models, but CCP imposes a tremendous computational cost when conducting a transient analysis in a three-dimensional (3D) model which reflects the real geometry of reactors. In particular, the detailed flow features of reactive gases induced by 3D geometric effects need to be considered for the precise calculation of radical distribution of reactive species. Thus, an alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 50 publications
1
41
0
Order By: Relevance
“…I, resulting in a densely populated region where is high and correspondingly reaction rate is large. Similar phenomenon was also observed in other literature [34]. Figure 10 shows the normalized deposition rate versus wafer radius, and the number densities of O, O2 + and SiO as well.…”
Section: Plasma Simulationssupporting
confidence: 87%
“…I, resulting in a densely populated region where is high and correspondingly reaction rate is large. Similar phenomenon was also observed in other literature [34]. Figure 10 shows the normalized deposition rate versus wafer radius, and the number densities of O, O2 + and SiO as well.…”
Section: Plasma Simulationssupporting
confidence: 87%
“…f ðeÞ is the assumed electron energy distribution function (EEDF). 25,26 The mean electron energy transport equation is as follows:…”
Section: Model Descriptionmentioning
confidence: 99%
“…where n e is the mean electron energy density, C e is the mean electron energy flux, and S e is the mean electron energy source term. 25,26 The mean electron energy flux is expressed as…”
Section: Model Descriptionmentioning
confidence: 99%
“…143,144) Kim and Lee analyzed the effects of electrode spacing and a 3D gas flow from a shower head for a SiH 4 =NH 3 =H 2 =He discharge. 143,144) For PECVD discharges, PIC simulations are computationally expensive because of the relatively high gas pressure of Torr order and high plasma density. Recently, Lee et al demonstrated an approach to PIC simulation for CCP deposition with the advantage of decreased computational time through parallelization using graphic processing units (GPUs).…”
Section: Simulations Of Plasma Dynamics and Chemical Reactions In Plamentioning
confidence: 99%